Effect of whitening toothpastes on wear and roughness of ormocer and methacrylate-based composites - Augusto, Marina Gullo [UNESP]; Borges, Alessandra Bühler [UNESP]; Pucci, César Rogério [UNESP]; Mailart, Mariane Cintra [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (My University, 2018)
Purpose: To investigate the effects of whitening toothpastes over the wear and surface roughness of ormocer and methacrylate composites. Methods: Cylindrical specimens (n=120) were prepared using methacrylate-based composites (Filtek Z350 XT, TPH3 and GrandioSO) and a pure-ormocer composite (Admira Fusion). Brushing abrasion (100,000 strokes) was performed using whitening toothpastes containing different abrasives: alumina (Colgate Ultrawhite), perlite (CloseUp Whitening) and sodium bicarbonate (Kin Progressive Whitening). Wear and roughness alteration were evaluated. Additional analyses of microhardness, degree of conversion and scanning electron microscopy were also performed. Results: Data were separately analyzed with Kruskal-Wallis and ANOVA tests. Statistically significant differences were found for the composites and whitening toothpastes (P<0.05). For all toothpastes, GrandioSO showed lower wear than Z350 XT and Admira Fusion, although non-significant differences in relation to TPH3 were observed. For perlite and bicarbonate-based toothpastes, Z350 XT, Admira Fusion and TPH3 did not present significant differences among them for wear. For alumina-based toothpaste, Z350 XT showed higher wear than TPH3, while Admira Fusion showed intermediate values. Higher wear and roughness alteration were observed after using alumina-containing toothpaste. All composites tested showed increased roughness after brushing. Z350 XT presented the lowest roughness alteration, while Admira Fusion the highest.